Frequency of perfume in 398 children's cosmetics - Marjorie Uber; Mariana A.P. Morgan; Maria Carolina Schneider; Izabella R.R. Gomes; Renata R. Imoto; Vânia O. Carvalho; Kerstin T. Abagge (Elsevier, 2024)
Objective: Perfume (Parfum) or fragrance is a natural or synthetic cosmetic ingredient added to emit a pleasant aroma or to improve the odor of a cosmetic formula. It is a mixture of substances, not revealed by the manufacturer, which may contain ingredients with allergenic potential, endocrine disruptors, and other possible harmful effects on human health. This study aims to analyze children's cosmetics labels to assess the presence of Perfume. Methods: The researchers randomly visited points of sale in Curitiba, the capital of a southern Brazilian state; in order to catalog the largest possible number of children's cosmetics items. Results: 398 children's cosmetics were analyzed and found Parfum on 295 (74.1 %) of the labels, including 90.4 and 79,1 % of the shampoos and wet wipes, respectively. Conclusion: Exposure of children's skin to fragrances can lead to local side effects such as allergies, but also to systemic effects, and the lack of knowledge of the general population and health professionals about its possible deleterious effects emphasizes the importance of changes in the regulation of cosmetics aiming to reduce the use of this ingredient.